To Determine The Effect Of Chemical Preparations Used In The Administration Of Hoplocampa Testudinea Count - Azimjon Anarboev; Komila Akhmedjanova; Abbos Nurjobov; Bekmurod Niyozkulov (International Scientific and Current Research Conferences, 2021)
The article considers the spread of apple trees in apple orchards grown on the territory of the Republic, the damage and Gazelle-D 55% k in the fight against this pest. The results of an experiment on the biological effectiveness of a chemical preparation are presented.